If p(x) = x³-4x²+x+6, then show that p(3) = 0 and hence factorie p(x)
factorise bhi krna hai
Answers
Answered by
1
Answer:
» x³ - 4x² + x + 6 = 0
Sum of even powers = sum of odd powers.
Therefore, (x + 1) is the factor.
» -1 | 1 -4 + 1 + 6
| -1 + 5 + -6
______________
| x² - 5x + 6 = 0
» x² - 5x + 6 = 0
» x² - 3x - 2x + 6 = 0
» x (x - 3) - 2 (x - 3) = 0
» (x - 2) (x - 3) = 0
Also (x + 1) is the factor,
Therefore, (x + 1) (x - 2) (x - 3) = 0
Hence, p (3) = 0.
Answered by
1
Answer:
x³ -4x² +x+6
(3)³-4(3)²+(3)+6
27-36+3+6
0
Similar questions